Biochemical Observations in Patients Suffered From Acute and Chronic Kidney Diseases with Reference to Thyroxi - Omar K Hassan (Journal of Global Pharma Technology, 2016)
Blood samples of acute kidney injury (AKI) patients (20) ;chronic kidney disease(CKD) patients (20) and normal persons(20), were collected from the central dialysis unit and private clinical diagnostic laboratories in Mosul city/Iraq during the period from (Jan. to March.2018), for investigation of blood urea, serum creatinine, serum thyroxin (T4) and serum total protein, Albumin and Globulin. Results reviled that only urea and creatinine were significantly reduced in AKI patients, but all studied parameters except albumin were significantly reduced in CKD patients in comparison with normal persons. Health significance of all parameter s levels was discussed.